Development of video learning media based on history to improve social studies achievement - Azri Isnaini Tanjung; Ichwan Azhari; R. Mursid (Himpunan Pengembang Kurikulum Indonesia, 2025)
The limited availability of interactive media that integrates local historical content has been one of the main obstacles in achieving optimal learning outcomes in Social Studies (IPS) at the elementary school level. This research aims to develop a local-history-based instructional video to improve the cognitive achievement of fourth-grade students in Social Studies. The research employs a Research and Development (RnD) approach, utilizing a modified ADDIE model that consists of three stages: analysis, design, and development. Experts in instructional assessment, subject content, media, language, and educational practitioners validated the media. The evaluation process included both formative and summative evaluations. Formative evaluation was conducted through expert validation and small-group trials, while the summative evaluation focused on field testing involving 23 students. Data were collected through observation, interviews, questionnaires, and cognitive tests. The results showed that the developed video media was categorized as highly valid and practical. Based on N-Gain and t-test analysis, there was a significant improvement in students’ cognitive learning outcomes. This indicates that instructional video media based on local history is effective in enhancing learning achievement and student engagement in Social Studies. Further research is recommended to explore its impact on affective and psychomotor domains. Abstrak Keterbatasan ketersediaan media interaktif yang mengintegrasikan konten sejarah lokal menjadi salah satu kendala utama dalam pencapaian hasil belajar yang optimal pada mata pelajaran Ilmu Pengetahuan Sosial (IPS) di jenjang sekolah dasar. Penelitian ini bertujuan untuk mengembangkan media video pembelajaran berbasis sejarah lokal guna meningkatkan capaian hasil belajar kognitif peserta didik kelas IV SD. Penelitian ini menggunakan metode Research and Development (RnD) dengan model ADDIE yang dimodifikasi menjadi tiga tahap, yaitu analisis, desain, dan pengembangan. Evaluasi dilakukan dalam dua bentuk, yaitu evaluasi formatif dan sumatif. Evaluasi formatif dilaksanakan melalui validasi oleh ahli instrumen penilaian, ahli materi, ahli media, ahli bahasa, dan praktisi pendidikan, serta uji coba terbatas. Evaluasi sumatif dilakukan melalui uji lapangan terhadap 23 peserta didik. Teknik pengumpulan data menggunakan observasi, wawancara, angket, dan tes kognitif. Hasil penelitian menunjukkan bahwa media video yang dikembangkan termasuk dalam kategori sangat valid dan praktis. Analisis data menggunakan N-Gain dan uji t menunjukkan adanya peningkatan signifikan pada hasil belajar kognitif peserta didik. Temuan ini membuktikan bahwa media video pembelajaran berbasis sejarah lokal efektif dalam meningkatkan pencapaian hasil belajar serta keterlibatan peserta didik dalam pembelajaran IPS. Penelitian lanjutan disarankan untuk mengkaji pengaruh media terhadap ranah afektif dan psikomotorik. Kata Kunci: hasil belajar; IPS; sejarah lokal; video pembelajaran